Field effect in amorphous carbon nanomesh directly synthesized from phase-separated polymer blends - Son, Su-Young; Park, Min; Lee, Dong Su; Lee, Sungho; Han, Jiyoon; Jung, Gun Young; Joh, Han-Ik (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Nano engineering of semi-metallic graphene can create graphene nanostructures such as nanoribbon and nanomesh for applications in electronic devices. Graphene materials manipulated by delicate patterning technology have exhibited semiconducting behavior, but the complex processes and degradation of the graphene during processing can be a bottleneck for the practical applications. Herein, a direct patterning approach to fabricate mesh-type carbon materials with a nanohole array was developed using phase-separated polyacrylonitrile (PAN)/poly (methyl methacrylate) (PMMA) blends. Carbon nanomeshes (CNMs) with various neck widths less than 100 nm were obtained by controlling the mixing ratio of PAN to PMMA. Gate dependent ambipolar transport behavior was observed even though the CNM exhibits imperfect crystallinity due to the catalyst-free preparation. Based on the systematic investigation of the temperature dependent electrical transport of the CNM-based field effect transistor, it was demonstrated that the charge conduction in CNMs is dominated by variable range hopping between localization states. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: LARGE-AREA; TRANSPORT-PROPERTIES; GRAPHENE NANOMESH; LAYER GRAPHENE; FABRICATION; MOBILITY; ELECTRODES; NANOSHEETS; GROWTH